2010
DOI: 10.1614/ipsm-d-09-00036.1
|View full text |Cite
|
Sign up to set email alerts
|

Control Techniques and Management Strategies for the Problematic Navua sedge (Cyperus aromaticus)

Abstract: Navua sedge, a member of the Cyperaceae family, is an aggressive weed of pastures in Fiji, Sri Lanka, the Malay Peninsula, Vanuatu, Samoa, the Solomon Islands, and Tahiti and is now a weed of pastures and roadsides in north Queensland, Australia. Primarily restricted to areas with an annual rainfall exceeding 2,500 mm (98.4 in), Navua sedge is capable of forming dense stands, smothering many tropical pasture species. Seventeen herbicides were field tested at three sites in north Queensland, with glyphosate, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(64 citation statements)
references
References 32 publications
1
55
0
2
Order By: Relevance
“…It is a native of tropical Africa but has now spread widely and become problematic in many southwest Pacific islands and in the tropical north of Queensland, Australia (Benson 1992;Black 1984;Parsons and Cuthbertson 1992;Vitelli et al 2010). Being unpalatable, C. aromaticus provides very low feed value to cattle, which facilitates its spread in pastures (Vitelli et al 2010), where it can consequently establish a significant presence. Coupled with this invasion, the species can spread at an alarming rate across large areas within a short period of time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a native of tropical Africa but has now spread widely and become problematic in many southwest Pacific islands and in the tropical north of Queensland, Australia (Benson 1992;Black 1984;Parsons and Cuthbertson 1992;Vitelli et al 2010). Being unpalatable, C. aromaticus provides very low feed value to cattle, which facilitates its spread in pastures (Vitelli et al 2010), where it can consequently establish a significant presence. Coupled with this invasion, the species can spread at an alarming rate across large areas within a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Each seed head produces approximately 250 seeds, and C. aromaticus is capable of producing 450 to 550 million seeds ha −1 (Karan 1975). Studies conducted by Vitelli et al (2010) showed that soil seedbank densities of 44,400 to 56,700 viable seeds m −2 are present in areas of dense C. aromaticus infestation. Mature seeds are lightweight and are thus readily dispersed by wind over short distances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para esta espécie, o herbicida halosulfuron-methyl representa a principal opção, já tendo sido relatada sua seletividade por não resultar em redução no crescimento e promover fitotoxicidade à mamoneira, quando aplicado em pós-emergência (Silva et al, 2010). Este herbicida pertence ao grupo químico das sulfonilureias e possui, como mecanismo de ação, a inibição da enzima acetolactato sintase (ALS) e elevada eficácia de controle para espécies ciperáceas (Vitelli et al, 2010).…”
Section: Introductionunclassified
“…Outro herbicida do grupo das sulfonilureias com o mecanismo de ação de inibição da enzima acetolactato sintase (ALS), que apresenta elevada eficácia de controle para tiririca e outras ciperáceas, é o halosulfuron-methyl (Vitelli et al, 2010). Apesar disto, este herbicida está registrado para aplicação em pós-emergência somente na cultura da cana-de-açúcar (MAPA, 2013).…”
Section: Introductionunclassified